Analisis Yuridis Terhadap Penjatuhan Putusan Kasasi Dalam Tindak Pidana Korupsi (Studi Putusan Nomor 4950 K/Pid.Sus/2023) - Fiktorius Kehidupan Dao (JUNCTO: Jurnal Ilmiah Hukum, 2026)
Corruption as an extraordinary crime causes multidimensional harm, including losses to state finances and the national economy. One high-profile corruption case examined by the Supreme Court is Decision Number 4950 K/Pid.Sus/2023 involving Surya Darmadi. This study aims to analyze the irregularities in the legal reasoning of the cassation judgment, particularly regarding the omission of liability for state economic losses. This research employs normative legal research using statutory, case, and analytical approaches. Data were collected through a literature review of primary, secondary, and tertiary legal materials and analyzed using descriptive qualitative methods with deductive reasoning. The findings indicate that the cassation decision deviates from the judgments at the first instance and appellate levels, which had clearly imposed liability for state economic losses. The exclusion of such liability potentially weakens the principle of state loss recovery and undermines the objectives of sentencing in corruption cases.